KENDALA DAN UPAYA MEWUJUDKAN SUPREMASI HUKUM - Indrati Rini (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
The most material Iaiv resources comes from the living aspiration in the society. The Imv supremacy is enforced by the law enforcers who have experienced the handicaps in the society Public hearing is a tool of the law communication between government and society.